Strategi Lembaga Amil Zakat Dompet Dhuafa Singgalang dalam Menghimpun Dana Sosial Umat di Provinsi Sumatera Barat - Alfian Alfian; Muhammad Aidil Akbar (Universitas Islam Negeri Imam Bonjol Padang, 2026)
This study is motivated by the suboptimal implementation of fundraising strategies at Dompet Dhuafa Singgalang, resulting in low public awareness of fundraising activities and a decline in fundraising outcomes over the last three years. The study aims to analyze the fundraising strategies implemented by Dompet Dhuafa Singgalang, including dialogue fundraising, corporate fundraising, multichannel fundraising, and donor retention and development strategies. This research employs a descriptive qualitative method. Primary data were obtained through field observations and interviews with branch heads and division heads of Dompet Dhuafa Singgalang, while secondary data were collected from monthly and annual audit documents. Data were analyzed through data collection, examination, analysis, and conclusion drawing. The findings show that: (1) dialogue fundraising was implemented through volunteer activites during Ramadhan 2025, fundraising booths, and one-on-one conversations with the community; (2) corporate fundraising was conducted through partnerships with government and non-government institutions aimed at improving community welfare; (3) multichannel fundraising was carried out through active management of digital platforms, including the official website and social media such as Instagram, Facebook, Twitter, and YouTube; and (4) donor retention and development strategies were implemented through maintaining relationships with donors via regular messages and souvenirs.